An Overview of Gene Editing Modalities and Related Non-clinical Testing Considerations. (May 2023) - Vats, Srishti; Ballesteros, Cristina; Hung, Selly; Sparapani, Samantha; Wong, Karen; Haruna, Julius; Li, Christian; Authier, Simon
Gene therapy has become an important modality for a wide range of therapeutic indications with a rapid increase in the number of therapeutic candidates being developed in this field. Understanding the molecular biology underlying the gene therapy is often critical to develop appropriate safety assessment strategies. We aimed to discuss some of the commonly used gene therapy modalities and common preclinical toxicology testing considerations when developing gene therapies. Non-viral gene delivery methods such as electroporation, microinjection, peptide nanoparticles and lipid nanoparticles are deployed as innovative molecular molecular construct which are included in the design of novel gene therapies and the associated molecular biology mechanisms have become relevant knowledge to non-clinical toxicology. Viral gene delivery methodologies including Adenovirus vectors, Adeno-Associated virus vectors and Lentivirus gene therapy vectors have also advanced considerably across numerous therapeutic areas, raising unique non-clinical toxicology and immunological considerations. General toxicology, biodistribution and tumorigenicity are the pillars of non-clinical safety testing in gene therapies. Evaluating the tumorigenicity potential of a gene editing therapy often leverages molecular pathology while some translational challenges remain. Toxicology study design is entering a new era where science-driven customized approaches and program specific considerations have become the norm.